A revised sizing method for borehole heat exchangers in the Chinese national standard based on reliability and economy. (May 2022) - Zhi, Chengqiang; Yang, Xiuqin; Zhou, Xiang; Tu, Shuyang; Zhang, Xu
Abstract: The total length of borehole heat exchangers (BHEs) is an essential issue for ground source heat pump (GSHP) systems. An insufficient number of BHEs may lead to the attenuation of long-term performance and may fail to meet the cooling or heating demands of buildings. Meanwhile, too many BHEs that exceed the system reliability requirement lead to excessive investment. In China, the total length of BHEs calculated using the current Chinese national standard GB50366-2009 is increased when a constant is simply multiplied by engineers; this approach is not economic nor reasonable. Therefore, this study revised the calculation method of the total length of BHEs in Chinese national standards by introducing a parameter called temperature penalty ( T p ) to ensure the long-term performance of GSHP systems and minimise the economic cost. A comparison of system reliability under the original BHE length calculation method and the optimised method was performed by simulation. The simulation method was verified through experimental measurement. Regression equations for the thermal conductivity of soil, specific heat capacity of soil, thermal conductivity of grout, daily operation time and T p were also proposed.